2020
DOI: 10.3390/cells9030568
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Steamed and Freeze-Dried Mature Silkworm Larval Powder Prevents Hepatic Fibrosis and Hepatocellular Carcinogenesis by Blocking TGF-β/STAT3 Signaling Cascades in Rats

Abstract: Hepatocellular carcinoma (HCC) is the leading cause of cancer-related deaths worldwide and the majority of HCC patients occur with a background of hepatic fibrosis and cirrhosis. We have previously reported the hepatoprotective effects of steamed and freeze-dried mature silkworm larval powder (SMSP) in a chronic ethanol-treated rat model. Here, we assessed the anti-fibrotic and anti-carcinogenic effects of SMSP on diethylnitrosamine (DEN)-treated rats. Wistar rats were intraperitoneally injected with DEN once … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 64 publications
(92 reference statements)
2
4
0
Order By: Relevance
“…We did not show any side effects such as weight change or decreased dietary intake in rats treated with SMSP. In addition, the previous study with DEN-induced hepatocellular carcinoma rat model have shown that the administration of 1 g/kg of SMSP for 16 weeks does not induce any toxicity compared to the normal group [29]. These results demonstrate that the supplementation of 1-10 g/kg rat body weight of SMSP for 4-16 weeks would be safe.…”
Section: Discussionsupporting
confidence: 54%
“…We did not show any side effects such as weight change or decreased dietary intake in rats treated with SMSP. In addition, the previous study with DEN-induced hepatocellular carcinoma rat model have shown that the administration of 1 g/kg of SMSP for 16 weeks does not induce any toxicity compared to the normal group [29]. These results demonstrate that the supplementation of 1-10 g/kg rat body weight of SMSP for 4-16 weeks would be safe.…”
Section: Discussionsupporting
confidence: 54%
“…IL-6 and TGF-β1 also operate as positive stimulators of the cytoplasmic transcription factor STAT3 in HSCs, promoting fibrosis by stimulating the synthesis of fibrotic marker proteins. Cirrhosis and carcinogenesis are the results of long-term fibrosis 109 . Upregulation of TGF-β1 has been identified as a wound healing process that protects against the spread of hepatocyte proliferation associated with genetic abnormalities following injury 51 , 52 .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that inflammation is involved in pathological features during regenerative fibrotic nodule formation, which replaces normal functional liver parenchyma to remodel the vasculature in the liver and ultimately compromises liver function [39][40][41][42]. Histologically, the inflammatory responses to toxic signals of DEN and influence fibrotic load have been characterized by our [18] and other studies [43]. These…”
Section: Prolonged Single-diet Den Administration Within Drinking Wat...mentioning
confidence: 72%